2008
DOI: 10.1002/hrm.20241
|View full text |Cite
|
Sign up to set email alerts
|

Human resource manager insights on creating and sustaining successful reduced‐load work arrangements

Abstract: Although human resource managers have critical insights into the successful implementation of reduced‐load work arrangements, relatively few studies focus on their perspective. These arrangements are a growing work form for employees who choose to work less than full‐time with a commensurate decrease in salary. Qualitative data analysis was used to identify key success factors noted in interviews with 52 HR managers in 39 companies. Individual employee characteristics (e.g., self‐regulatory work habits) were v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…While it is commonly assumed that professionals and managers share similar attitudes with respect to conduct and performance standards, 305 Discussing Work-Life Fit research has shown otherwise (Leicht & Fennel, 2001). Consistent with prior studies (Fried, Kossek, Lee, & MacDermid, 2008), we anticipate that even though Company A established an initiative to enhance access to FWAs, support of the program will not be equal across managers, in part because some managers may view the merits of flexible work (or the program itself) with varying levels of enthusiasm/skepticism.…”
Section: Attitudinal Dispositionsupporting
confidence: 54%
“…While it is commonly assumed that professionals and managers share similar attitudes with respect to conduct and performance standards, 305 Discussing Work-Life Fit research has shown otherwise (Leicht & Fennel, 2001). Consistent with prior studies (Fried, Kossek, Lee, & MacDermid, 2008), we anticipate that even though Company A established an initiative to enhance access to FWAs, support of the program will not be equal across managers, in part because some managers may view the merits of flexible work (or the program itself) with varying levels of enthusiasm/skepticism.…”
Section: Attitudinal Dispositionsupporting
confidence: 54%
“…Older workers' accommodative and developmental climates were assessed with scales developed by Kooij (2010), which were based on previous research on supportive climates (Armstrong‐Stassen and Schlosser, 2008; Dikkers et al., 2004). Accommodative climate items were constructed based on research on accommodative practices, cultures, and stereotypes about older workers (Abraham and Hansson, 1995; Dikkers et al., 2004; Friede et al., 2008; Gaillard and Desmette, 2008), and focus on accommodating older workers in a process of gradual withdrawal from the workforce. Items for development climate were based on previous research on this topic (Armstrong‐Stassen and Schlosser, 2008; Maurer et al., 2003), and focus on encouragement to use skills and knowledge of older workers, and to develop older workers.…”
Section: Methodsmentioning
confidence: 99%
“…The climates for older workers in organizations can be classified along these theoretical dimensions of the aging process: drawing from disengagement theory it can be expected that an accommodative climate encourages gradual withdrawal from work demands to prepare aging workers for retirement (see, e.g. Dikkers et al., 2004; Friede et al., 2008; Kooij, 2010; Ngo et al., 2009; Remery et al., 2003). In line with the logic of activity theory, a development climate stresses continuous development of employees, such that employees and their organizations improve their functioning and performance (Armstrong‐Stassen and Schlosser, 2008; Kraimer et al., 2011).…”
Section: The Role Of Unit Climate In Continuing Workingmentioning
confidence: 99%
“…The subordinate contributes greater levels of trust, commitment, loyalty, and assistance to the leader in exchange for greater resources (Yukl, 2006). Thus, researchers have suggested that a high-quality manager-subordinate relationship may increase access to and usage of work-family programs by favored subordinates (Friede, Kissek, Lee, & MacDermid, 2008;Major & Lauzon, 2010;Major & Morganson, 2011;Poelmans & Beham, 2008;Straub, 2012), and empirical research has shown that LMX is associated with managers' implementation of idiosyncratic work-family-supportive arrangements (Major & Lauzon, 2010). Golden (2006) found evidence that higher quality LMX relationships are associated with greater use of telecommuting by subordinates.…”
Section: Situational Contextsmentioning
confidence: 96%